The Geopolitical Conceptual Shifting: Forward A Critical Geopolitical Approach In Ir. - benmessahel, alaerrahmane (المجلة الجزائرية للأمن الإنساني, 2024)
This topic falls within the interest of theoretical studies in international relations, which link epistemic shifts in geopolitical thought and their relationship to shifts in global politics. This article aims to monitor the development of geopolitical thought through three main parts. The first part presents classical geopolitics, introducing geopolitical thought in the pre-Cold War phase. The second section deals with Cold War geopolitics and the revival of geopolitics, while the last section represents post-Cold War geopolitics and the theoretical foundations of critical geopolitics. The study concluded that the conceptual and intellectual shift in geopolitics coincides with the developments in international relations in theory and reality.